Adsorption of binary hydrocarbon gas mixtures on activated carbon: Theoretical prediction of the binary equilibrium data - Sang Chul Jung; Mi Jin Jeon; Yong Woo Jeon (Energy Reports, 2020)
Experimental binary equilibrium data for the adsorption of hydrocarbon mixtures on activated carbon at given temperature are presented and discussed. Pure-component adsorption isotherms were fitted by using Langmuir model. Then adsorption isotherms were determined for different binary mixtures. Adsorption isotherms of binary mixtures were calculated using the real adsorbed solution theories, which requires the calculation of the activity coefficients for the components in the adsorbed phase. Activity coefficients are evaluated using Margules activity model and UNIQUAC model. We described the adsorption equilibria using proposed model parameters with taken to be equal to those of VLE. The results show that, except for a few systems, the calculated results were in good agreement with experimental adsorption equilibrium data.
Keywords: 330; Adsorption equilibria; Gas-adsorbed equilibrium; Real adsorption solution theory